The correlation of the change in vertical angulation of the beam in the bisecting technique to the length of the tooth - Kharidah Khairullah Nabihah; Muhammad Novo Perwira Lubis (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: To find out the correlation between changes in vertical angle beam in periapical radiography of bisecting techniques to the length dimension of the tooth. Materials and Methods: This study was a study using laboratory experimental methods. The samples used in this study were incisor 1, incisor 2, canine, premolar 1, premolar 2, molar 1, and molar 2 region 1. Based on the results of the minimum number of samples at G*power, measures of effect size f (0.4512937), α err prob (0.05), power (1-β err prob) (0.8), number of groups (5), number of measurements (2), corr among rep measurements (0.6), nonpersphericity correction € ( (1). All teeth are treated in the form of a change in angle from the standard angle recommended by White and Pharoah to -10°, -5°, 0°, +5°, +10° , +10° in each tooth using the Dental X-ray unit of Veraview V080 type EX-2 70 kV. 7 mA. Results: Based on Saphiro-Wilk, Kruskall-Wallis, and Paired t-test tests, it is known that there is a significant relationship between the actual length of the tooth and the length of the radiograph result in the change of angle + foreshortening, and the change of angle - the elongation. However, this does not apply to molar teeth 1 and 2 at positive angle changes However, this does not apply to molar teeth 1 and 2. A change in angle -10° is a change in angle with a better degree. Conclusion: There is a correlation between the change in vertical angle beam in the periapical radiography of bisecting techniques to the length dimension of the tooth.